2016
DOI: 10.15537/smj.2016.4.12665
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the origin and branching patterns of the iliolumbar artery and its implications on pelvic and vertebral surgery

Abstract: Objectives:To evaluate the origin, distribution pattern, branches, and neighboring structures of the iliolumbar artery (ILA) concerning the anterolateral surgical approaches to the spine.Methods:This study was performed in the Anatomy Department of Medical School, Mersin University, Mersin, Turkey between 2014 and 2015. Pelvises of 11 male formalin-fixed human cadavers were dissected by anterior and posterior approaches under surgical microscope. The origins, distribution patterns, calibers, and distances to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…Valchkevich Dzmitry et al8 , Waseem Al Talalwah et al11 &Teli CG et al12 observed that the origin of Iliolumbar Artery was from the posterior division in 73.3%(22) 77.90%& 80%(32) respectively, a findingwhich was similar with our study. While in other studies ofparul et al7 , Ravi Shankar Gadagi et al9 , TuranKoç et al 10 ,Kiray A et al13, Yuvaraj Maria Francis 14 ,Rusu MC et al15 , the iliolumbar artery originated from trunk of IIAin 66.66% (16), 36.67%(11), 57.14%(12), 71.4% (30), 75%, 52.50% respectively -a findingwhich was different from our study.A comparison of variations with respect to the origin of the iliolumbar artery (ILA), with different studies is tabulated in table 2.…”
supporting
confidence: 91%
“…Valchkevich Dzmitry et al8 , Waseem Al Talalwah et al11 &Teli CG et al12 observed that the origin of Iliolumbar Artery was from the posterior division in 73.3%(22) 77.90%& 80%(32) respectively, a findingwhich was similar with our study. While in other studies ofparul et al7 , Ravi Shankar Gadagi et al9 , TuranKoç et al 10 ,Kiray A et al13, Yuvaraj Maria Francis 14 ,Rusu MC et al15 , the iliolumbar artery originated from trunk of IIAin 66.66% (16), 36.67%(11), 57.14%(12), 71.4% (30), 75%, 52.50% respectively -a findingwhich was different from our study.A comparison of variations with respect to the origin of the iliolumbar artery (ILA), with different studies is tabulated in table 2.…”
supporting
confidence: 91%
“…Interestingly, they reported the ILA to be absent in relatively many specimens (n = 14). The absence of the ILA was also described in the study conducted by Koc et al [17], where four ILAs were absent, and their branches originated from other nearby arteries. The results of the present meta-analysis show that the ILA was absent in 1.25%.…”
Section: Discussionsupporting
confidence: 64%
“…Kiray et al ( 40 ) reported an average ILA diameter of 3.7 ± 0.7 mm, and Teli et al ( 25 ) reported an average ILA diameter of 3.5 ± 0.5 mm. Koc et al ( 23 ) reported that the ILA diameter originating from the main trunk of the IIA was smaller than that originating from the posterior branch of the IIA. In addition, the iliac lumbar artery mainly originates from the main internal iliac artery and less from the posterior branch of the IIA and CIA ( 25 , 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the incidence of T2ELs was also associated with the internal iliac artery ranging from 0 to 3.8% ( 21 ), and some investigators believe it was related to the iliolumbar artery ( 21 , 22 ). The iliolumbar artery and lumbar artery are connected through collateral circulation and can communicate with the fourth lumbar artery ( 23 25 ). However, no studies have investigated the association between the iliolumbar artery and T2ELs after EVAR.…”
Section: Introductionmentioning
confidence: 99%